The Influence of Perceived Usefulness, Perceived Ease of Use, and Trust in Dana E-Wallet on Students' Interest in Shopping at MSMEs in Sumbawa Besar - Muhammad Najib Rabbani; Wilia Ismiyarti (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze the effect of Perceived Usefulness, Perceived Ease of Use, and Trust on students' purchase intention in using the DANA e-wallet for transactions at micro, small, and medium enterprises (MSMEs) in Sumbawa Besar. This research employed a quantitative approach with a total sample of 190 respondents consisting of university students who are DANA e-wallet users in Sumbawa Besar Regency. The sampling technique used was purposive sampling, with criteria limited to students who had previously used the DANA e-wallet for MSME transactions. The results indicate that Perceived Usefulness and Trust have a positive and significant effect on students' purchase intention, while Perceived Ease of Use shows a positive but not statistically significant effect when tested partially. Simultaneously, Perceived Usefulness, Perceived Ease of Use, and Trust have a significant effect on purchase intention toward MSMEs in Sumbawa Besar. These findings suggest that students' purchase intention is more strongly influenced by perceived functional benefits and trust in the digital payment system rather than by ease of use alone. This condition is consistent with the current phenomenon in Sumbawa Besar, where an increasing number of MSMEs and local merchants have adopted QRIS-based payment systems, making e-wallets such as DANA an integral part of students' daily transaction activities.